Arene–perfluoroarene interactions confer enhanced mechanical properties to synthetic nanotubes. Issue 8 (10th February 2022) - Roesner, Emily K.; Asheghali, Darya; Kirillova, Alina; Strauss, Michael J.; Evans, Austin M.; Becker, Matthew L.; Dichtel, William R.
Abstract : Arene–perfluoroarene interactions resulted in enhanced crystallinity between analogous perhydro- and perfluoro macrocycles in a supramolecular nanotube assembly. Abstract : Supramolecular nanotubes prepared through macrocycle assembly offer unique properties that stem from their long-range order, structural predictability, and tunable microenvironments. However, assemblies that rely on weak non-covalent interactions often have limited aspect ratios and poor mechanical integrity, which diminish their utility. Here pentagonal imine-linked macrocycles are prepared by condensing a pyridine-containing diamine and either terephthalaldehyde or 2, 3, 5, 6-tetrafluoroterephthalaldehyde. Atomic force microscopy and synchrotron in solvo X-ray diffraction demonstrate that protonation of the pyridine groups drives assembly into high-aspect ratio nanotube assemblies. A 1 : 1 mixture of each macrocycle yielded nanotubes with enhanced crystallinity upon protonation. UV-Vis and fluorescence spectroscopy indicate that nanotubes containing both arene and perfluoroarene subunits display spectroscopic signatures of arene–perfluoroarene interactions. Touch-spun polymeric fibers containing assembled nanotubes prepared from the perhydro- or perfluorinated macrocycles exhibited Young's moduli of 1.09 and 0.49 GPa, respectively. Fibers containing nanotube assemblies reinforced by arene–perfluoroarene interactions yielded a 93% increase in the Young's modulus over the perhydro derivative, up to 2.1 GPa. These findings demonstrate that tuning the chemical composition of the monomeric macrocycles can have profound effects on the mechanical strength of the resulting assemblies. More broadly, these results will inspire future studies into tuning orthogonal non-covalent interactions between macrocycles to yield nanotubes with emergent functions and technological potential.